Characterization of microbial populations associated with different organic fertilizers - Natalia Escobar; Nelson E Arenas; Sara M Marquez (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Bacterial and fungal communities represent key bioindicators of soil quality and are essential for the maintenance of nutrient availability. Our purpose was to characterize the bacterial and fungal biodiversity associated with different compost mixtures, comparing microbiological indicators regarding the soil quality. Methods Compost samples and mixtures were prepared (15:1 final ratio) with chemical fertilizer, animal manures (bovine, swine, and poultry) and green waste (such as tomato waste and leaves). Bacterial and fungal isolation and identification were performed through standard phenotypic methods. Statistical methods to assess differences between treatments included Shannon diversity, Chi-square tests, Bray-Curtis clustering, and Canonical Correspondence Analysis. Results Streptomyces species, Gram-positive bacteria, were commonly found in differing abundances in all samples. Gram-positive species were predominant in soils amended with vegetable green waste while Gram-negative bacteria were more abundant in samples with chemical fertilizer. Fungal abundance increased in poultry manure and chemical fertilizers. Conclusion Our findings suggested that organic matter recycling and composting resulted in the shifting of biodiversity in bacterial and fungal populations which might be associated with the availability of certain nutrient sources provided by the composting materials.